ANALISIS PENGARUH IKLAN TELEVISI, EKUITAS MEREK, DAN DAYA TARIK CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - Atika Wiguna; Suyoto Suyoto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This was a quantitative research aiming to find out the effect of every variable studied namely advertisement on television, brand equity, attraction of celebrity endorser towards the decision of buying Wardah cosmetic product. The sampling technique used in this research was non probability technique in a form of purposive sampling method that determines samples based on certain criteria. The population of this research was all students in University of Muhammadiyah Purwokerto, and the samples of this research involved 125 respondents. The methods of data analysis used in were validity test, reliability test, classic assumption test, multiple regressions analysis, coeffiecient of determination, and hypothesis test. The result of analysis showed that advertisement on television partially affected positively towards the decision of buying, and the hypotesis was accepted with tobtained 3,582 > ttable 1,979, equity affected positively towards the decision of buying, and the hypothesis was accepted with tobtained 6,317 > ttable 1,979, celebrity endorser affected towards the decision of buying with tobtained 2,841 > ttable 1,979. Furthermore, the independent variables (advertisement on television, brand equity, and celebrity endorser) simultaneously affected the dependent variable (decision of buying) . Keywords: Advertisement on Television. Brand Equity, Celebrity Endorser, and Decision of Buying.